1973
DOI: 10.1007/bf01398860
|View full text |Cite
|
Sign up to set email alerts
|

On test charge potentials in collisional plasmas

Abstract: The effect of electron-electron collisions on the potential of a slowly moving test charge in a plasma is considered. A new dipole-like term is found. IntroductionThe electric field of a moving test charge in a uniform plasma has recently received increased attention. Thus, Montgomery and others [1,2] considered the far-field potential of a test charge in a collisionless plasma and found that it can decrease as the inverse cube of the distance. The effect of collisions has been considered recently [3,4] using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…In a classical electronion plasma [1,2], an isolated ion is shielded by nondegenerate Boltzmann distributed electrons, and hence one [3] replaces Q by Z i e and λ by the electron Debye radius λ De = (k B T e /4πn 0 e 2 ) 1/2 , where Z i is the ion charge state, e the magnitude of the electron charge, k B the Boltzmann constant, T e the electron temperature, and n 0 the unperturbed electron number density. For a slowly moving test charge in collisionless [4] and collisional [5,6] plasmas, there appear additional far-field potentials decreasing as inverse cube and inverse square of the distance between the test charge and the observer. In a collisionless dusty plasma [7][8][9] with Boltzmann distributed electrons and ions, a micron-sized negatively charged isolated dust is shielded by both positive ions and electrons.…”
mentioning
confidence: 99%
“…In a classical electronion plasma [1,2], an isolated ion is shielded by nondegenerate Boltzmann distributed electrons, and hence one [3] replaces Q by Z i e and λ by the electron Debye radius λ De = (k B T e /4πn 0 e 2 ) 1/2 , where Z i is the ion charge state, e the magnitude of the electron charge, k B the Boltzmann constant, T e the electron temperature, and n 0 the unperturbed electron number density. For a slowly moving test charge in collisionless [4] and collisional [5,6] plasmas, there appear additional far-field potentials decreasing as inverse cube and inverse square of the distance between the test charge and the observer. In a collisionless dusty plasma [7][8][9] with Boltzmann distributed electrons and ions, a micron-sized negatively charged isolated dust is shielded by both positive ions and electrons.…”
mentioning
confidence: 99%
“…Surprisingly, however, starting in the 1950's several authors (Neufeld & Ritchie 1955; Tappert 1967; Montgomery, Joyce & Sugihara 1968) discovered that a test charge moving uniformly is not exponentially screened, but generates the field of a quadrupole in a collisionless plasma. The restriction to a collisionless plasma was lifted in later papers (Yu, Tegeback & Stenflo 1973; Schroeder 1975), where it was shown that the far field of a moving test charge is that of a dipole with strength of order q τ t V , where q is the charge, τ t the collision time as measured by t and V the velocity. This dipole form ensures that in Minkowski space the contribution of particles to the effective mass falls off rapidly with distance beyond the Debye radius.…”
Section: Effective Thermal Mass In a Plasma In Minkowski Spacementioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23] Electrostatic shielding of a moving charge is a fundamental problem in plasma physics. [13][14][15][16][17][18][19][20][21][22][23] Electrostatic shielding of a moving charge is a fundamental problem in plasma physics.…”
Section: Introductionmentioning
confidence: 99%
“…In a thermal plasma the far-field electrostatic potential of a freely moving test charge is not Debyeshielded like that of a stationary charge because the motion of the test charge introduces in the expression for potential a relatively slowly decaying inertial term that does not contain the characteristic exponential shielding. [18][19][20] In the classical moving test-charge problem, one is concerned with the linear kinetic response of the background plasma to a moving point charge. [14][15][16][17] When the test charge is suprathermal, there also appears behind it potential oscillations.…”
Section: Introductionmentioning
confidence: 99%